Identifying trade-offs between ecosystem services, land use, and biodiversity: a plea for combining scenario analysis and optimization on different spatial scales - Seppelt, Ralf; Lautenbach, Sven; Volk, Martin (Current opinion in environmental sustainability, 2013)
Research on mitigating land use conflicts is characterized by a variety of projects from the global to various sub-global scales. These projects are aiming at disentangling feedbacks within changing socio-environmental systems to identify strategies for sustainable resource use. Our review shows that any global analysis benefits from systematic synthesis of sub-global research from various scales, while sub-global investigations require embedding in global scenarios. There is an urgent need for improved methods to identify trade-offs at all scales as scenario analysis frequently results in a discrete set of options. We argue that the use of optimization algorithms including Pareto-frontiers combined with scenario analysis can provide efficient options for sustainable land use from global to sub-global scales.
Gesehen am 10.12.2018